Therapeutic effect of traditional Chinese medicine on diabetic sarcopenia: a systematic review and meta-analysis of preclinical studies - Zhang, Ruiting; Liu, Yingzhe; Zhu, Lin; Li, Dongxia; Pan, Xiangbin (Frontiers in Endocrinology, 2026)
BackgroundDiabetic sarcopenia (DS) is an emerging complication of diabetes. Although clinical treatment options remain inadequate, preliminary evidence suggests that Traditional Chinese Medicine (TCM) holds therapeutic promise. This study aims to systematically evaluate the existing preclinical evidence for TCM treatments in diabetic sarcopenia.MethodsWe conducted a meta-analysis of animal studies investigating TCM interventions for DS. The initial literature search cutoff date was June 2024, with an updated search conducted during manuscript revision in November 2025. The search covered all records from seven databases from their inception to November 2025. Data analysis is performed using Review Manager 5.3 software. A fixed-effect model was selected when heterogeneity among studies was insignificant (P ≥ 0.1 or I² ≤ 50%); otherwise, a random-effects model was used. The robustness of the primary outcomes was assessed through sensitivity analysis. Publication bias was evaluated using Egger’s test and funnel plots. Additionally, meta-regression was employed to explore potential sources of heterogeneity.This study has been registered on the PROSPERO platform (Registration Number: CRD42024596404).ResultsThe meta-analysis demonstrated that TCM intervention significantly increased gastrocnemius muscle weight [SMD = 1.85, 95% CI (1.07, 2.63), P < 0.00001] and muscle cross-sectional area [SMD = 2.68, 95% CI (1.63, 3.73), P < 0.00001], while improving muscle tissue morphology and grip strength [SMD = 1.57, 95% CI (0.49, 2.65), P = 0.004]. Notably, TCM exerted a bidirectional regulatory effect on body weight: significantly increasing it in diabetic cachexia models [SMD = 0.73, P = 0.02] while reducing it in obesity with sarcopenia models [SMD = -1.97, P < 0.00001]. A significant reduction in blood glucose levels was also observed [SMD = -3.13, P < 0.00001]. Mechanistically, preclinical evidence suggests that specific TCM interventions may modulate protein turnover homeostasis, potentially by activating the IGF1-PI3K-Akt-mTOR synthetic pathway and inhibiting the FoxO/Ubiquitin-Proteasome degradation pathway, alongside optimizing the pathological microenvironment.ConclusionCurrent preclinical evidence suggests that specific TCM interventions may show potential in alleviating Diabetic Sarcopenia in animal models by improving muscle mass, strength, and metabolic function. Certain formulations appeared to exhibit a bidirectional regulation of body weight, which may reflect a context-dependent metabolic impact. However, due to the prevalent lack of blinding and allocation concealment in the included studies, the reported efficacy may be systematically overestimated. Consequently, current evidence remains preliminary. Future research must strictly adhere to ARRIVE guidelines and standardize interventions to generate robust preclinical data, paving the way for high-quality clinical trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD4202459640.